Metabolomics of beta-blockers - Tan, Ian Yong Ming. (2010)
Carvedilol is a nonselective β-blocker with multiple properties, including antioxidant properties, α-adrenergic blocking effects and inhibitory effects on calcium channels. It has been used in the clinical treatment of hypertension and congestive heart failure. While it is known that each enantiomer of Carvedilol exhibits different pharmacological activity, their effects at the cellular level are not well understood. In order to better understand how each enantiomer affects cells, the metabolite profiles of vascular smooth muscle cells (A7r5) were analysed after incubating with S- and R-Carvedilol separately using GC-MS technology. 27 metabolites were shown to be commonly expressed in all the samples and of the 27 metabolites, 8 metabolites were identified to be of particular interest. These metabolites are lactic acid, alanine, succinic acid, 5-oxoproline and proline, spermidine, threonine and aspartic acid. These metabolites were closely related to the clinical effects of Carvedilol and the differences in the levels of metabolites, as analysed by GC-MS, further supported the known differences in the pharmacological effects of the two enantiomers. The results will lead to a better understanding of the metabolic pathway of Carvedilol and subsequently facilitate the development of novel drug applications utilising the special properties of Carvedilol.